The environmental benefits of urban open green spaces - Rakhshandehroo, Mehdi; Mohd Yusof, Mohd Johari; Arabi, Roozbeh; Parva, Mohammad; Nochian, Ashkan (Faculty of Design & Architecture, Universiti Putra Malaysia, 2017)
Most of the scientific papers on urban planning and sustainable development begin by emphasizing the multiple benefits of urban open green space. When it comes to the benefits of urban green and open space, one should concern on the facilities provided to promote human or societal wellbeing, either directly or indirectly. In this study, a review of identified peer-reviewed literature from the most popular online databases was carried out and its contribution to improve our understanding of urban open green spaces and their environmental benefits to the human being are discussed. These many benefits cover various areas such as natural conservation which increases biodiversity of flora and fauna, affecting urban climate by reduction of air temperature and urban heat islands, improving air quality, decreasing air pollution and carbon sequestration, noise reduction and cleaning up contaminants. As urban open green spaces contribute to human and social wellbeing, they are essential for livable and sustainable cities.